Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1121/1.1631937
|View full text |Cite|
|
Sign up to set email alerts
|

Atmospheric absorption in the atmosphere up to 160 km

Abstract: This paper describes new algorithms, not previously available, for predicting atmospheric absorption of sound at high altitudes. A basis for estimating atmospheric absorption up to 160 km is described. The estimated values at altitudes above 90 km must be considered as only approximate due to uncertainties about the composition of the atmosphere above 90 km and simplifying assumptions. At high altitudes, classical and rotational relaxation absorption are dominant, as opposed to absorption by molecular vibratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
203
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(209 citation statements)
references
References 9 publications
5
203
0
1
Order By: Relevance
“…High-resolution profiles of the infrasonic/acoustic wave attenuation were obtained. The results were in good agreement with the calculations published by Sutherland and Bass (2004). Observations of the acoustic waves transmitted from the ground using the RASS loudspeaker were not successful because of the background noise of the rocket motor.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…High-resolution profiles of the infrasonic/acoustic wave attenuation were obtained. The results were in good agreement with the calculations published by Sutherland and Bass (2004). Observations of the acoustic waves transmitted from the ground using the RASS loudspeaker were not successful because of the background noise of the rocket motor.…”
Section: Discussionsupporting
confidence: 82%
“…The onboard infrasonic/acoustic waves measurements showed that the attenuation was small at frequencies less than 50 Hz. This corresponds with theoretical studies that report less attenuation at lower frequencies 11) . There might have been…”
Section: Discussionmentioning
confidence: 99%
“…Long-range ground-to-ground infrasound propagation is most efficient in the stratosphere [Fee et al, 2013], as the absorption in this waveguide is relatively small [Sutherland and Bass, 2004]. However, a sufficiently strong stratospheric circumpolar vortex in the direction of propagation is required to trap infrasound in the stratosphere.…”
Section: Passive Acoustic Remote Sensingmentioning
confidence: 99%
“…Attenuation due to intrinsic absorption can be treated perturbatively [Jensen et al, 1994], using effective absorption coefficients (z) [Sutherland and Bass, 2004].…”
Section: Appendix A: Ray Tracingmentioning
confidence: 99%
“…The roll-off at higher frequencies (>3 Hz) is more pronounced in the seismic data than infrasonic data, emphasizing that the infrasonic data may be more representative of the broadband trigger signal. This may also relate to frequencydependent anelastic attenuation and scattering, which is more severe for seismic energy in the volcanic edifice than in the air [Thelen et al, 2009;Sutherland and Bass, 2004].…”
Section: Power Spectramentioning
confidence: 99%